Optimization of micropropagation by different concentration of vitamins and sucrose in St. John’s Wort (Hypericum Perforatum) - Khakpour, Sahar; Motallebi-Azar, Alireza; Hosseini, Bahman; Alizadeh-Salte, Saeede; Hasani, Abbas (Plant Breeding and Seed Science, 2015)
In order to approach optimal micropropagation of Hypericum perforatum, it will be necessary to optimize shoot proliferation stage in in vitro culture. This study was conducted to investigate the effects of different concentrations of B group vitamins; Thiamine HCl, Pyridoxine HCl, Nicotinic acid (control and 100 fold of MS) and Sucrose (30 and 40 g.l-1) on shoot proliferation. For this purpose, Stems with one node were taken from in vitro shoots and cultured on MS medium. All cultures kept at 16h light/8h photoperiod and 25 ±2 oC in growth chamber. Results showed that the highest number of shoots and leaves were achieved when ex-plants cultured in media containing 40 g.l-1 sucrose with 100 fold of MS vitamins. The highest shoots and leaf length were obtained with medium supplemented with 30 g.l-1 sucrose. Nicotinic acid concentrations had an important role in length of the leaves. The highest number of nodes achieved in the media containing 40 g.l-1 sucrose with both concentrations of Nicotinic acid. After two month growing plantlets, light (LGN) and dark glands number (DGN) were counted. Maximum number of LGN was observed in the media containing 30 g.l-1 sucrose with 100 fold of Thiamine and Pyridoxine. However, The Highest number of DGN achieved in the media containing 40 g.l-1 sucrose with 100 fold of Thiamine or Pyridoxine. Increasing of sucrose and vitamins concentrations were efficiently improved in vitro proliferation and some morphological attributes without negative side effects. Therefore, use of high levels of sucrose and vitamins were useful on micro-propagation of Hypericum perforatum.